Disinfection of polyether impression materials with hydrogen peroxide solution containing silver ion - Farahnaz Nejatidanesh; Kamran Poushang Bagheri; Mojtaba Shahtousi; Mohsen Talaei; Omid Savabi (Isfahan University of Medical Sciences, 2010)
Introduction: Disinfection of dental impressions is mandatory for decreasing the risk of infection transmission to dental laboratory. Polyethers are one of the most popular and precise impression materials. The aim of this study was to evaluate the disinfecting potential of 2% Sanosil on polyether impression materials wia immersion and spray methods.Materials and Methods: Sixty three circle specimens (1 cm diameter and 2 mm thickness) of polyether impression materials (Impregum F) were contaminated with Staphylococcus Areus (ATCC 29213), Enterococcus Feacalis (ATCC 51299), and Candida Albicans (PTCC 5027) except for control samples, all specimens were immersed in or sprayed with 2% Sanosil for 5 and 10 minutes (5 samples for each disinfection methods and 1 control). Tripsin was used for separating of microorganisms. 1, 1/2 and 1/4 concentrations of the tripsination solution were analyzed microbiologically for Colony-Forming Units (CFU). The number of CFUs per milliliter was counted at 24 and 48 hours for the bacteria and 72 hours for Candidia Albicans. Mann-Whitney and Wilcoxon tests were used for data analysis (α = 0.05).Results: With both spray and immersion methods, the number of CFUs decreased with increasing the disinfecting time and increased with longer incubation time. The CFU counting of Staphylococcus Areus in 5 and 10 minutes immersion in 2% Sanosil were significantly less than spraying method (p value < 0.05). The difference between the two methods in 5 minute disinfection was not significant for Enterococcus Feacalis, however in 10 minute disinfection the immersion proved significantly more effective. The number of CFUs for Candidia Albicans after an incubation of 72 hours was less with 5 minute immersion compared to 5 minute spray. The two methods did not show significant differences in 10 minute disinfection.Conclusion: Spraying with and immersion in 2% Sanosil have high level bacteriocidal effect on Staphylococcus Areus (100% and 99.99%, respectively) and less effect on Enterococcus Feacalis (88% with spraying and 96% with immersion). 2% Sanosil has high effectiveness in disinfection of Candida Albicans (99% with spraying and 99.99% with immersion). Key words: Disinfection, Dental impression materials, Dental disinfectants, Candidia Albicans, Enterococcus Feacalis, Staphylococcus Areus